Temporal Evolution of Poststroke Cognitive Impairment Using the Montreal Cognitive Assessment. Issue 1 (January 2017) - Nijsse, Britta; Visser-Meily, Johanna M.A.; van Mierlo, Maria L.; Post, Marcel W.M.; de Kort, Paul L.M.; van Heugten, Caroline M.
Abstract : Background and Purpose—: The Montreal Cognitive Assessment (MoCA) is nowadays recommended for the screening of poststroke cognitive impairment. However, little is known about the temporal evolution of MoCA-assessed cognition after stroke. The objective of this study was to examine the temporal pattern of overall and domain-specific cognition at 2 and 6 months after stroke using the MoCA and to identify patient groups at risk for cognitive impairment at 6 months after stroke. Methods—: Prospective cohort study in which 324 patients were administered the MoCA at 2 and 6 months post stroke. Cognitive impairment was defined as MoCA<26. Differences in cognitive impairment rates between 2 and 6 months post stroke were analyzed in different subgroups. Patients with MoCA score <26 at 2 months, who improved by ≥2 points by 6 months, were defined as reverters. Logistic regression analyses were used to identify determinants of (1) cognitive impairment at 6 months post stroke and (2) reverter status. Results—: Between 2 and 6 months post stroke, mean MoCA score improved from 23.7 (3.9) to 24.7 (3.5), P <0.001. Prevalence of cognitive impairment at 2 months was 66.4%, compared with 51.9% at 6 months ( P <0.001). More comorbidity and presence of cognitive impairment at 2 months were significant independent predictors of cognitive impairment 6 months post stroke. No significant determinants of reverter status were identified. Conclusions—: Although cognitive improvement is seen ⩽6 months post stroke, long-term cognitive deficits are prevalent. Identifying patients at risk of cognitive impairment is, therefore, important as well as targeting interventions to this group. Abstract : Supplemental Digital Content is available in the text.